Development of iSpeak: Augmentative and Alternative Communication for Malaysian Population - HAZIZI, NUR IZZAH; Omar, Nurul Aswa (Applied Information Technology And Computer Science, 2024)
Augmentative and Alternative Communication (AAC) refers to a variety of communication techniques that can be used in addition to or in place of speech or writing and for those who have difficulties expressing or understanding spoken or written language. iSpeak system is used to enhance decision-making quality more methodically and lower the likelihood of making mistakes. The feedback after using the system prototype will be considered for the upcoming iteration of prototypes, which will help to enhance system functioning. To utilise the system, both users and administrators need an email and a password. System functioning is examined to confirm that system development objectives are met. Testing is done to make sure the system was designed to fully benefit its users.